COMPARATIVE STUDY OF INDONESIAN AND MALAYSIAN ENVIRONMENTAL LAWS - Rachmat, Muhammad Yusuf; Handayati, Nur; Prawesthi, Wahyu; Citra, Pawitra (Proceeding of International Conference on Multidisciplinary Research, 2024)
This research is a comparative study of two laws in the world, Indonesian environmental law and Malaysian environmental law, two Southeast Asian nations with diverse ecosystems and environmental challenges. Indonesia and Malaysia were once subject to long periods of colonial rule and occupation. It was during these periods that English laws and Dutch laws gradually introduced into the two respective countries with varied consequences. This study explores the historical context, legal frameworks, and challenges faced by both countries in their efforts to protect and conserve their natural environments. Through a systematic examination of these aspects, this research aims to provide insights into the strengths and weaknesses of their environmental legal systems and offers recommendations for enhancing environmental governance